The influence of prenatal dexamethasone administration before scheduled full-term cesarean delivery on short-term adverse neonatal outcomes: a retrospective single-center cohort study - Pei, Jiaojiao; Chen, Jiao (Frontiers in Pediatrics, 2024)
Objective: There has been a gradual increase in the prevalence of cesarean section deliveries and more healthcare professionals are considering the prophylactic use of corticosteroids before planned full-term cesarean sections. However, the association between dexamethasone administration before full-term cesarean delivery and short-term adverse neonatal outcomes is unclear. This study analyzed the disparities in short-term adverse neonatal effects in neonates born via full-term elective cesarean delivery with or without antenatal dexamethasone treatment. Study design: This single-center retrospective cohort study involved neonates aged 37-39 weeks. The primary neonatal outcomes included various short-term adverse events, including neonatal admission to the neonatal intensive care unit, neonatal access to the special care baby unit, transient neonatal respiratory distress, respiratory distress syndrome, and the requirement of intravenous antibiotics or ventilatory support. Multiple logistic regression analysis was used to assess the association between these outcomes and dexamethasone exposure while adjusting for covariates. Results: Of the 543 neonates included in the study, 121 (22.2%) had been exposed to prenatal dexamethasone. When compared with the control group, the dexamethasone-exposed group exhibited significantly higher rates of transient neonatal respiratory distress, respiratory distress syndrome, administration of intravenous antibiotics, the need for ventilatory support, and longer duration of neonatal hospitalization (P < 0.05). The association between dexamethasone exposure and short-term adverse neonatal outcomes remained significant after adjusting for potential confounders (odds ratio: 12.76, 95% confidence interval: 6.9-23.62, P < 0.001).The dexamethasone-exposed group had a higher likelihood of experiencing short-term adverse outcomes when compared with non-exposed neonates, suggesting that dexamethasone may have detrimental effects on infants delivered at full term. This implies the importance of exercising caution when contemplating the use of antenatal corticosteroids.